2023
DOI: 10.3389/fimmu.2023.1043380
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the association and causal effect between white blood cells and psoriasis using large-scale population data

Abstract: IntroductionPsoriasis is a chronic inflammatory disease of the skin. A few studies have shown that psoriasis is an immune-mediated disease in which multiple immune cells play crucial roles. However, the association between circulating immune cells and psoriasis remains elusive.MethodsTo explore the role of circulating immune cells in psoriasis, 361,322 individuals from the UK Biobank (UKB) and 3,971 patients with psoriasis from China were included to investigate the association between white blood cells and ps… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 78 publications
1
12
0
Order By: Relevance
“…This underscores the necessity for early monitoring of in ammatory markers and proactive in ammation management, a trend gaining traction in the clinical landscape of immune-mediated in ammatory diseases. Current consensus leans towards employing the neutrophil/lymphocyte ratio (NLR) and platelet/lymphocyte ratio (PLR) in psoriasis assessment, with studies demonstrating their association with the disease, albeit not directly correlating with severity [22][23][24][25]. Notably, biologic therapies have shown e cacy in reducing NLR and PLR levels, highlighting their utility as biomarkers in monitoring disease trajectory and treatment response [35][36][37][38].…”
Section: Discussionmentioning
confidence: 99%
“…This underscores the necessity for early monitoring of in ammatory markers and proactive in ammation management, a trend gaining traction in the clinical landscape of immune-mediated in ammatory diseases. Current consensus leans towards employing the neutrophil/lymphocyte ratio (NLR) and platelet/lymphocyte ratio (PLR) in psoriasis assessment, with studies demonstrating their association with the disease, albeit not directly correlating with severity [22][23][24][25]. Notably, biologic therapies have shown e cacy in reducing NLR and PLR levels, highlighting their utility as biomarkers in monitoring disease trajectory and treatment response [35][36][37][38].…”
Section: Discussionmentioning
confidence: 99%
“…These findings suggest that MASLD exacerbates skin manifestations and inflammation of psoriatic lesions. Additionally, a Mendelian randomization study suggested that a rise in white blood cell count and neutrophils could be risk factors for the onset of psoriasis ( 49 ). Thus, the increased levels of these cells observed in the MASLD group might indicate an exacerbation of psoriasis when associated with MASLD.…”
Section: Discussionmentioning
confidence: 99%
“…Here, we propose a new intermediate trait category for use in proxying drug targets in IMD: immune cell abundance. There is substantial animal model, observational and MR evidence[2126] implicating immune cell dysregulation in the pathogenesis of immune-mediated disorders, ranging from roles of T H 2 cells, eosinophils, and neutrophils in allergic conditions like asthma[27,28] and eczema[29,30] to expansion of certain T helper lymphocyte and B lymphocyte lineages in autoimmune diseases such as systemic lupus erythematosus (SLE)[31], multiple sclerosis[32] and rheumatoid arthritis[5]. Furthermore, approved drug targets for IMD are usually classed as immunosuppressants or immunomodulators, which alter the balance of immune blood cells in their course of on-target action.…”
Section: Introductionmentioning
confidence: 99%